C1q/TNF-related protein-9 suppresses inflammation in synovial cells from patients with osteoarthritis. (3rd September 2022) - Dong, F; Jiang, M; Zhang, Z; Li, F; Lian, Y
Abstract : Objective: Synovial inﬂammation contributes to cartilage degeneration and osteoarthritis (OA) development. Targeting the inflammation process may provide a promising strategy for OA treatment. It has been demonstrated that C1q/tumour necrosis factor-related protein-9 (CTRP9) has immunosuppression capabilities. Thus, we conducted this study to investigate the role of CTRP9 in OA and its therapeutic potential. Method: The expression level of CTRP9 was quantified in peripheral blood mononuclear cells (PBMCs), serum, and synovial cells (SCs) isolated from OA patients by quantitative polymerase chain reaction and enzyme-linked immunosorbent assay. The relationship between the expression level of CTRP9 and the disease activity of OA was determined. The inflammation-suppressing effects of CTRP9 were assessed in vitro. Results: The expression level of CTRP9 was increased in the PBMCs and serum of OA compared to healthy controls. The serum level of CTRP9 was found to be positively correlated with erythrocyte sedimentation rate, C-reactive protein, and visual analogue scale score. In addition, CTRP9 protein suppressed the expression of pro-inflammatory cytokines, including tumour necrosis factor-α, interleukin-6, and interleukin-1β, in PBMCs and SCs in vitro. CTRP9 was increased in OA patients and positively correlated with the disease activity. The recombinant CTRP9 had inflammation-suppressing activities in vitro. Conclusion: CTRP9 may have therapeutic potential for treating OA. Osteoarthritis (OA) is characterized as cartilage destruction resulting from synovial inﬂammation (1–6 ). According to the clinical symptoms and levels of inflammation, OA has been divided into primary generalized osteoarthritis (PGOA) and erosive inflammatory osteoarthritis (EIOA) (7 ). The only available treatment for OA is joint replacement. Thus, it is necessary to develop novel and effective therapeutic strategies to treat OA. Because synovial inﬂammation contributes to OA development, targeting the inflammation process may provide a promising strategy for OA treatment. Previous investigations showed that pro-inflammatory factors promoted OA development (8–10 ), while anti-inflammatory factors suppressed it (11–14 ). Thus, we conducted the present study to investigate the role of C1q/tumour necrosis factor-related protein-9 (CTRP9), an anti-inflammatory factor (15 ), in OA, and its therapeutic potential.